Investigation of small lung lesion detection for lung cancer screening in low dose FDG PET imaging by deep neural networks - Guo, Haijun; Wu, Jun; Xie, Zongneng; Tham, Ivan W. K.; Zhou, Long; Yan, Jianhua (Frontiers in Public Health, 2022)
Purpose: FDG PET imaging is often recommended for the diagnosis of pulmonary nodules after indeterminate low dose CT lung cancer screening. Lowering FDG injecting is desirable for PET imaging. In this work, we aimed to investigate the performance of a deep learning framework in the automatic diagnoses of pulmonary nodules at different count levels of PET imaging. Materials and Methods: Twenty patients with 18F-FDG-avid pulmonary nodules were included and divided into independent training (60%), validation (20%), and test (20%) subsets. We trained a convolutional neural network (ResNet-50) on original DICOM images and used ImageNet pre-trained weight to fine-tune the model. Simulated low-dose PET images at the 9 count levels (20×10^6, 15×10^6, 10×10^6, 7.5×10^6, 5×10^6, 2×10^6, 1×10^6, 0.5×10^6 and 0.25×10^6 counts) were obtained by randomly discarding events in the PET list mode data for each subject. For the test dataset with 4 patients at the 9 count levels, 3307 and 3384 image patches were produced for lesion and background, respectively. The receiver-operator characteristic (ROC) curve of the proposed model under the different count levels with different lesion size groups were assessed and the areas under the ROC curve (AUC) were compared. Results: The AUC values were greater than 0.98 for all count levels except for 0.5 and 0.25 million true counts (0.975 (CL 95%, 0.953-0.992) and 0.963 (CL 95%, 0.941-0.982), respectively). The AUC values were 0.941(CL 95%, 0.923-0.956), 0.993(CL 95%, 0.990-0.996) and 0.998(CL 95%, 0.996-0.999) for different groups of lesion size with effective diameter (R)<10mm, 10-20mm, and >20mm, respectively. The count limit for achieving high AUC (≥0.96) for lesions with size R<10mm and R>10mm were 2 million (equivalent to an effective dose of 0.08mSv) and 0.25 million true counts (equivalent to an effective dose of 0.01mSv), respectively. Conclusion: All of the above results suggest that the proposed deep learning based method may detect small lesions less than 10mm at an effective radiation dose less than 0.1mSv. We investigated the advantages and limitations of a fully automated lung cancer detection method based on deep learning models for data with different lesion sizes and different count levels, and gave guidance for clinical application.